What is a good PhD program in ophthalmology?: Students’ perspective - N, Mwangi; H, Rono; Arunga, Simon; F, Mdeme (Journal of Ophthalmology of Eastern Central and Southern Africa, 2018)
Access to doctoral studies is increasing and the impact of PhD programs is generally understood to be positive. However, the lack of clarity about what a PhD entails can be a barrier to student entry into the programs. During the pre-entry period, students need to consider the reasons for choosing to take PhD and the value expected from it. In practice, this involves complex considerations related to personal, institutional, logistical and PhD program characteristics. As such, prospective students would benefit from a reflection on these factors in advance of registering for the PhD. Realising that there is a limited published literature on what makes a PhD ‘good’, in this paper we explore the factors that contribute to students’ perception of a good scholarly engagement. We use an interview format to report on some broad areas of relevant consideration. We conclude that sustained student motivation, effective supervision, adequate facilities and a supportive environment are pertinent for the learning that makes a PhD ‘good’.
Keywords: PhD; Doctorate; Doctoral students; Eye health; Ophthalmology